Effective fundraising for nonprofits real-world strategies that work - Bray, Ilona M. 1962- (El Segundo, CA : Nolo, 2025)
"The success of a nonprofit depends on its ability to raise donations from individuals, companies, and institutions. This book includes advice and stories from more than 50 experienced fundraisers, foundation staffers, journalists, and more. It explains how to make a fundraising plan, work with individual donors, plan special events, use traditional and social media to engage supporters, and much more. This book also provides creative grassroots strategies and dozens of real-life success stories, and cuts out the jargon and "consultant speak" that's all too common in books about fundraising for nonprofits"--
Includes index.
115726
Keywords: Fund raising -- United States; Nonprofit organizations -- United States -- Finance